Direct Electrochemical Aptamer‐Based Detection of Digoxin. Issue 8 (24th February 2020) - Wijesinghe, Mahadurage Sachintha; Ngwa, Wilfred; Chow, Kwok‐Fan
Abstract: Here we report a signal‐on electrochemical aptamer‐based (E‐AB) sensor for the detection of digoxin at clinically relevant levels. Digoxin is a plant‐based medication that is prescribed to treat patients with congestive heart failure and chronic atrial fibrillation and atrial flutter. Digoxin has a narrow therapeutic range index of between 0.5 ng/mL and 2.0 ng/mL. The aptamer used in this study is a 50‐base DNA oligonucleotide that has been proven to have high affinity toward digoxin. One end of the aptamer is immobilized on a gold electrode surface and the other end is tagged with a methylene blue molecule, which is used as a redox label. Like other signal‐on E‐AB sensors, once the target binds to the aptamer‐modified electrode, the methylene blue reduction current increases. The developed E‐AB digoxin sensor provides a distinct and amplified peak current response in the therapeutic range of 0.5 ng/mL to 2.0 ng/mL in a phosphate buffer saline solution. The advantage of this detection method is that it allows an aptamer‐modified electrode to perform single‐step and reagentless sensing. We suggest this approach as a conceptual pathway to point‐of‐care E‐AB digoxin sensor design. Abstract : Here we report a signal‐on electrochemical aptamer‐based sensor for the detection of digoxin at clinically relevant levels. The sensing mechanism is based on the target‐induced conformational change of the digoxin‐specific aptamer sequence. The developed electrochemical aptamer‐based digoxin sensor provides a distinct and amplified peak current response in the therapeutic range of 0.5 ng/mL to 2.0 ng/mL in a phosphate buffer saline solution. We suggest this approach as a conceptual pathway to point‐of‐care digoxin sensor design.